Implementasi Uji Kompetensi Keahlian untuk Mengukur Kemampuan Akhir Siswa Kelas XII di SMKS Teknologi Industri Pinggir - Budy Satria; Candra Surya; Khelvin Ovela Putra; Tomy Nanda Putra; Budi Permana Putra; Irzon Meiditra; Dori Gusti Alex Candra; Nurdi Afrianto; Adi Prastya (PUAN INDONESIA, 2024)
Skills Competency Test (UKK) is a government program implemented by secondary level education units, especially for Vocational High School (SMK) students to measure students' competency achievements. On March 6 2024, a Skills Competency Test was carried out at the Pinggir Industrial Technology Vocational School as a form of participation in Community Service (PKM). The UKK participants were 12 class XII vocational school students majoring in Office Management Automation (OTKP). The aim of this PKM activity is to assist the Pinggir Industrial Technology Vocational School in carrying out skills competency exams so that quality graduates can enter the world of work professionally. The methods for implementing PKM are preparation, direction, mentoring, practice and assessment. The final assessment results from the UKK implementation were that there were 12 students with an average score of 92.25. The conclusion is that participants have passed and are competent in the field of Office Management Automation